1984
DOI: 10.1152/jn.1984.51.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Columnar organization of directionally selective cells in visual area MT of the macaque

Abstract: We recorded from single neurons in visual area MT of the macaque in order to examine the spatial distribution of its directionally selective cells. The animals were paralyzed and anesthetized with nitrous oxide. All MT neurons (n = 614) responded better to moving stimuli than to stationary stimuli. For 55% of the neurons, responses to moving stimuli were independent of stimulus color, shape, length, or orientation. For the remaining cells, stimulus length affected the response magnitude and tuning bandwidth bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
352
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 524 publications
(406 citation statements)
references
References 16 publications
47
352
3
Order By: Relevance
“…This type of "sequence regularity" closely matches that seen along single electrode penetrations in macaque MT (Albright et al 1984). As shown in Figure 2, the second array penetration (P2) happened to traverse a region of area MT that was also mapped by P1.…”
Section: Maps Of Direction-of-motion Preferencesupporting
confidence: 70%
See 3 more Smart Citations
“…This type of "sequence regularity" closely matches that seen along single electrode penetrations in macaque MT (Albright et al 1984). As shown in Figure 2, the second array penetration (P2) happened to traverse a region of area MT that was also mapped by P1.…”
Section: Maps Of Direction-of-motion Preferencesupporting
confidence: 70%
“…As previously pointed out by Albright et al (1984), the preferred direction maps reveal that gradual sequences of preferred axis of motion are commonly interspersed with 180 • reversals in preferred direction of motion. Adjacent recording sites that exhibit such 180 • directional discontinuities disappear in Figure 4.…”
Section: Maps Of Axis-of-motion Preferencesupporting
confidence: 56%
See 2 more Smart Citations
“…An object can contain contours of many different orientations which all move in the same direction as part of the object's motion. Both psychophysical and neurophysiological experiments have shown that the motion stream pools information from many orientations that are moving in the same direction to generate precise estimates of a moving object's direction and speed [19][20][21][27][28][29] . Lesions of the form system also show that, on its own, the motion system can make only coarse depth estimates 30,31 .…”
Section: Complementary Form and Motion Interactionsmentioning
confidence: 99%